Network analysis of the relationship between negative life events and depressive symptoms among adolescents: a comparison between males and females - Feng, Ran; Zhang, Qiongzhi; Wang, Lingzhi; Lei, Jingyu; Liu, Xuerong; Chen, Zhiyi; Li, Yanyan; Liao, Yujia; Gong, Jie; Ren, Jidong; An, Xianyong; Li, Xuemei; et al. (Frontiers in Pediatrics, 2025)
ObjectiveTo examine the network structure linking negative life events and depressive symptoms among adolescents in southwestern China, and to compare network characteristics between genders.MethodsNetwork analysis was used to assess associations between depressive symptoms and negative life events, identify core and bridge symptoms, evaluate global connectivity strength, and explore gender-specific differences in network structure. Participants completed the Center for Epidemiologic Studies Depression Scale (CES-D) and the Adolescent Self-Rating Life Events Checklist (ASLEC).ResultsData were collected from 104,552 adolescents aged 11–23 years. In the combined network, disease, academic stress, and being fined were the most central nodes, while flunking, broken heart, and academic stress served as key bridge symptoms between depressive symptoms and negative life events. Within the depressive symptom network, lack of happiness, depressed mood, feelings of failure, and sadness were the most central, with the strongest connection observed between hopelessness and feelings of failure. These core symptoms were consistent across genders. However, significant gender differences were found in network structure, global connectivity, and specific edges, with females exhibiting stronger overall symptom connectivity.ConclusionsThe adolescent depression network is characterized by stable core symptoms and gender-specific differences in connectivity and bridge symptoms. These findings highlight the potential importance of bridge symptoms for early identification and for developing gender-sensitive intervention strategies.